Optimal Abatement Technology Licensing in a Dynamic Transboundary Pollution Game: Fixed Fee Versus Royalty - Xu, Hao; Tan, Deqing (Computational economics, 2023)
Transboundary pollution poses a major threat to environment and human health. An effective approach to addressing this problem is the adoption of long-term abatement technology; however, many developing regions are lacking in related technologies that can be acquired by licensing from developed regions. This study focuses on a differential game model of transboundary pollution between two asymmetric regions, one of which possesses advanced abatement technology that can reduce the abatement cost and licenses this technology to the other region by royalty or fixed-fee licensing. We characterize the equilibrium decisions in the regions and find that fixed-fee licensing is superior to royalty licensing from the viewpoint of both regions. The reason is that under fixed-fee licensing, the regions can gain improved incremental revenues and incur reduced environmental damage. Subsequently, we analyze the steady-state equilibrium behaviors and the effects of parameters on the licensing performance. The analysis indicates that the myopic view of the regions leads to short-term revenue maximization, resulting in an increase in total pollution stock. Moreover, a high level of abatement technology or emission tax prompts the licensee region to choose fixed-fee approach, which is beneficial both economically and environmentally for two regions.